1997
DOI: 10.1002/(sici)1097-0010(199708)74:4<509::aid-jsfa827>3.3.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Protease Inhibitors of Chickpea (Cicer arietinum L) During Seed Development

Abstract: : Developing seeds of two chickpea varieties were collected on the 20th, 40th and 60th day after Ñowering (DAF) and analysed for trypsin inhibitors (TI). The varieties di †ered in their TI proÐles and activity units. The TI band and activity were not detectable at 20 DAF in the varieties Annigeri and BDN 9-3. Annigeri showed the highest total and speciÐc TI activity, and Ðve isoinhibitors at 40 DAF, which decreased to four at 60 DAF. The appearance and disappearance of TI bands during seed development indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…However, de novo synthesis and degradation of distinct variants cannot be ruled out. Harsulkar et al 20 reported changes in TI activity in developing seeds of chickpea collected at 20, 40 and 60 days after flowering that correlated with both the disappearance and appearance of TI during the course of seed development.…”
Section: Discussionmentioning
confidence: 99%
“…However, de novo synthesis and degradation of distinct variants cannot be ruled out. Harsulkar et al 20 reported changes in TI activity in developing seeds of chickpea collected at 20, 40 and 60 days after flowering that correlated with both the disappearance and appearance of TI during the course of seed development.…”
Section: Discussionmentioning
confidence: 99%
“…Other plants such as seeds of amaranth (Rodriguez et al, 1993), chickpea (Harsulkar et al, 1997), sunflower (Konarev et al, 2000), maize (Ellatif, 2014), and seeds or leaves of peppers (Montes et al, 2014) have been most extensively studied plants for their proteinase inhibitor contents. The most known proteinase inhibitors are active against digestive proteinases found in animals and microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies carried out by Harsulkar et al . (1997, 1999) with WBPI had also revealed a decrease of total as well as trypsin-like proteinase activity in H. armigera larvae as a result of which the growth of the early second instar was inhibited. WBTI was also found to significantly lower trypsin activity in the larvae of codling moth, Cydia pomonella (Linnaeus), but the elastase activity was higher than that in water controls (Markwick et al ., 1995).…”
Section: Discussionmentioning
confidence: 99%